(untitled) (American Journal of Islam and Society, 2006)
This beautifully produced work provides a gendered reading of the centrality of the Karbala commemorations among Shi`i communities. There is a strong Persian(ate) bias in the selections (only two papers really deal with practices in an Arab context). However, it represents the maturity of the state of Shi`i studies, having moved beyond the sensationalism of political obsessions following the Iranian revolution of 1979 and the textually based Orientalism of an earlier generation to considerations of actual practices, performances, understanding of texts, and enactments of doctrines. The Women of Karbala is a significant contribution to the study of Shi`i Islam in practice. Most of the papers are based on anthropological fieldwork in majoritarian communities. The collection could have benefited from some more historical studies (there are two studies on the Qajar period), textual studies, and examinations of Arab communities, as well as the increasing significance of the Shi`i diasporic communities in Europe and North America (one paper does nod in that direction). Another feature that would have enhanced the collection would be to interpret Shi`i more widely. For example, there is one paper on Bohra practices but none on the Zaydis and recent developments in the Yemeni highlands that have made Shi`i commemorations critical junctures of conflict ...